2023
DOI: 10.3390/healthcare11050704
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy among Japanese College Students: Association with Healthy Lifestyle and Subjective Health Status

Abstract: The improvement of health literacy (HL) is a critical issue for college students who are in the transitional period to adulthood and are establishing their subsequent lifestyles. The present study aimed to evaluate the current state of HL among college students and to explore the factors that influence HL. Moreover, it investigated the relationship between HL and health conditions. For this study, the researchers conducted an online survey of college students. The questionnaire consisted of the Japanese versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
0
7
0
1
Order By: Relevance
“…This combination was not observed in our sample. healthier lifestyle choices, such as making healthier dietary choices and increasing adequate physical activity levels (Yokoyama et al, 2023), and decreasing risk behaviors, such as smoking and harmful alcohol use (Svendsen et al, 2020). and colleagues stated that they found women to be more likely to co-use tobacco and alcohol, and they hypothesized that women in their sample were wealthier and more socially and financially independent (Ho et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This combination was not observed in our sample. healthier lifestyle choices, such as making healthier dietary choices and increasing adequate physical activity levels (Yokoyama et al, 2023), and decreasing risk behaviors, such as smoking and harmful alcohol use (Svendsen et al, 2020). and colleagues stated that they found women to be more likely to co-use tobacco and alcohol, and they hypothesized that women in their sample were wealthier and more socially and financially independent (Ho et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, this study found that those who engaged in physical activity above recommended levels were more likely to co‐use tobacco and alcohol. The basis for this finding is unclear because the higher health literacy among upper‐grade university students (Yokoyama et al, 2023) would support healthier lifestyle choices, such as making healthier dietary choices and increasing physical activity (Yokoyama et al, 2023) and decreasing risk behaviors, such as smoking and harmful alcohol use (Svendsen et al, 2020). This combination was not observed in our sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, en la presente investigación, la mayoría de los estudiantes catalogan el factor tecnológico como positivo para acceder a información de salud. Lo anterior, es coherente con los resultados de otros estudios (Yokoyama et al, 2023;Chen et al, 2023) sobre la alta consulta de estudiantes en internet para buscar información sobre el manejo de la salud y la prevención de enfermedades.…”
Section: El Entorno Social Cercano Como Determinante De La Cultura Fr...unclassified
“…Currently, research on HL among female workers in Japan is limited, both in comparison with Western countries and other research on HL in Japan. [ 23 24 25 26 ] For this reason, this study aimed to take a Hiroshima company as an example and analyze the influencing factors of HL scores to clarify the issue of the active participation of female employees.…”
Section: Introductionmentioning
confidence: 99%